Penilaian Kualitas Website E-Government Pejabat Pengelola Informasi dan Dokumentasi (PPID) Dengan Dimensi e-GovQual (Studi Pada Dinas Komunikasi dan Informatika Pemerintah Kota Probolinggo) - Sri Eko Wahyudi; Aryo Pinandito; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Public information is information resultant, saved, and / or received from with regard to the organizers and the implementation of other public bodies in accordance with the Act as well as other information relating to the public interest. Based on the Law of the Republic of Indonesia no. 14 years 2008 about public information openess explain that every one have right to get information as written in the Law on public Information. Based on result of interview with someone from Kominfo's Probolinggo city, dissemination information by